2013
DOI: 10.1590/sajs.2013/1015
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of CCA-treated timber in caterers’ fuelwood stocks in the Cape Town region

Abstract: Wood used as fuel under conditions of urban poverty is a source of air pollution. Fuelwood is harvested from peri-urban green areas or sourced as waste from industry or commerce, and used in the informal economy, both by households and by productive activities such as roadside catering. End-of-life timber may have previously been treated for protection, sometimes by impregnation with chromated copper arsenate (CCA). Combustion of CCA-treated timber could magnify the health and environmental risks associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…At least one wood sample collected from those fires was identified to have been CCA-treated. This was confirmed after comparing the results with the blank sample (Niyobuhungiro, 2012).…”
Section: Arsenic Volatilisation During Cca-treated Wood Combustionsupporting
confidence: 66%
See 1 more Smart Citation
“…At least one wood sample collected from those fires was identified to have been CCA-treated. This was confirmed after comparing the results with the blank sample (Niyobuhungiro, 2012).…”
Section: Arsenic Volatilisation During Cca-treated Wood Combustionsupporting
confidence: 66%
“…Fuel wood burning has been widely recognized as a significant contributor to ill-health through inhalation of such particulate matter in many developing countries (WHO, 2005). Our recent work has reported evidence that waste timber, previously treated with the insecticide CCA (chromated copper arsenate) is being used by informally operating street caterers in urban and peri-urban settings in the Cape Town region (Niyobuhungiro et al, 2012). The combustion of such wood, which may contain each of the elements Cr, Cu and As in the range of 500-6000 mg/kg, has previously been shown to lead to preferential volatilization of arsenic (Rogers et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A previous investigation indicated that CCA-treated wood used as fuel for open fires in street catering could be a significant potential public health problem in Cape Town. 1 In the latter study, CCA-treated wood samples were found in wood used for informal catering activities with the occurrence of treated wood being more prevalent in urban townships than in peri-urban areas of Cape Town. The wood was sourced from commercial and industrial sources.…”
Section: Introductionmentioning
confidence: 84%
“…The aim of this study was to compare the exposure to CCA-treated wood and the urinary levels of Cr, Cu and As amongst informal food caterers and household residents in an urban area and a peri-urban area in the Western Cape Province in South Africa, following on from a previous study. 1 The relationship between the usage of CCA-treated wood and urinary levels of Cr and Cu will be examined in another paper.…”
Section: Affiliationsmentioning
confidence: 99%
“…23 Present-day research on arsenic contamination in South Africa includes the search for arsenic-resistant bacterial genes in mining ash and the pollution levels in treated wood. [24][25][26][27] However, research in the field of arsenic contamination of soil at dip tanks -the focus of our study -has been limited. However, one study, conducted by Moremedi and Okonkwo 28 at Ka-Xikundu village close to the Luvuvhu River, also in the Vhembe district, reported high arsenic levels (above >1000 mg/kg) close to a dip site at the surface, and at 50-mm and 100-mm depths, and a significantly lower concentration of about 0.15 mg/ kg at a control site some distance away.…”
Section: East Coast Fever Cattle Dipping and Arsenic In South Africamentioning
confidence: 99%